English oral communication apprehension: A quantitative inquiry on Malaysian administrative staff in an educational institution - Mohd Zulfadli, Mat Husin; Nor Yazi, Khamis (Universiti Malaysia Pahang, 2024)
Even when employed, proficiency in English oral communication skills remains an asset. Mastering the skill is an advantage or could plausibly cause communication apprehension at the workplace. Comprehensive studies have covered English oral communication apprehension, yet the focus on workplace contexts still needs to be improved. Hence, this study investigates the oral communication apprehension levels of the administrative staff at a Malaysian public university. Utilising the Personal Report of Communication Apprehension 24 items (PRCA-24) instrument and a purposive sampling technique, the quantitative methodology of the study sampled one hundred fifteen administrative staff of the institution. The staff generally demonstrated moderate communication apprehension, with the highest in delivering public speeches using English. In addition, the t-tests and ANOVA scores showed no significant difference between the apprehension levels and investigated workplace variables, namely gender, education level, year of service and job grade among the staff. Nevertheless, the results provided sufficient evidence of English oral communication apprehension among the staff, which could intensify and jeopardise their job and productivity in the long run. The study implicates the need to strategies communication professional development training for the administrative staff to improve workplace English communication.